Subjective Outcomes of Carpal Tunnel Release in Patients with Diabetes and Patients without Diabetes - Afshar, Ahmadreza; Tabrizi, Ali; Tajbakhsh, Mojtaba; Navaeifar, Nasrin (Journal of Hand and Microsurgery, 2019)
Introduction This study aims to compare the subjective outcomes of carpal tunnel surgery in the patients with diabetes and patients without diabetes, and it tries to determine the difference between insulin-dependent and noninsulin-dependent patients.Materials and Methods This retrospective cohort study compares subjective outcomes of 35 patients with type 2 diabetes and 35 patients without diabetes who had a unilateral carpal tunnel release. None of the patients with diabetes had neuropathy. All the patients had surgery by a single surgeon with miniopen incision under local anesthesia. The patients were evaluated before surgery and 6 months after surgery using two Brigham and Women's Carpal Tunnel QuestionnairesResults Carpal tunnel release was improved based on symptom severity scale (SSS) and functional status scale scores in patients with diabetes and nondiabetic patients. However, the mean SSS scores were higher in patients without diabetes 6 months after the surgery. Comparison between the mean SSS scores of the patients with diabetes showed higher scores in noninsulin-dependent patients. In patients with diabetes, SSS scores were positively correlated with carpal tunnel syndrome and diabetes durations.Conclusion The outcomes of carpal tunnel release were improved in both patients with diabetes and patients without diabetes suffering from median nerve compression at the wrist. However, the duration of diabetes and its treatment can be related to the severity of the disease symptoms after the carpal tunnel releasing surgeries. In some diabetic patients, the severity of the symptoms was persistent.Level of Evidence This is a prognostic level IV study.
Keywords: carpal tunnel syndrome; diabetes; symptom severity scale; functional status scale